Catering Management Practices - Sharma, Jyoti S. (New Delhi, 2006)
Food is the most basic necessity of every living being besides air and water. As such the tradition of catering (i.e. cooking) is as old as the history of man. As an academic discipline, catering is taught in different courses of home science, food science and technology and hotel and tourism management. Catering is a perfect art and science. The present volume is a modest attempt in the direction of presenting valuable information on catering management, which is flourishing industry. Only most relevant aspects are taken for elaborate discussion. Definitely, the learner, i.e. trainees, trainers and all professionals in the field will find this most useful and informative.
Keywords: Caterers; Catering Management